Youth Violence in Germany: Examining the Victim–Offender Overlap During the Transition From Adolescence to Early Adulthood. (September 2018) - Erdmann, Anke; Reinecke, Jost
The victim–offender overlap is currently under discussion in criminology. However, the connection between victimization and offending over the life course still requires further investigation. The present study examines whether the victim–offender overlap is invariant during the transition from adolescence to early adulthood using seven consecutive waves of the German Research Foundation–funded self-report study "Crime in the Modern City, " which contain information about German students from the age of 14 to 20 years. The results indicate that the nature as well as the strength of the overlap changes over the period from adolescence to early adulthood. The introduced measurement of the relative victim–offender overlap indicates that with growing up, fewer victims are also offenders whereas the amount of offenders that are also victims remains stable. Longitudinal analyses based on latent growth and cross-lagged panel models further point out that the developments of victimization and offending are highly parallel processes that evince similar stability and mutual influence over the phase of youth and adolescence. However, the association between both weakens over age. In conclusion, our results suggest variance in the victim–offender overlap over the life course. This justifies the demand for further research and theory development on this criminological phenomenon.